Language tools for creating an image of the addressee in the epistolary texts of B. Pasternak - Ziamlianik, Tatsiana V. (Journal of the Belarusian State University. Philology, 2019)
The language tools for creating the recipient’s image in B. Pasternak’s letters to E. Pasternak, M. Tsvetaeva, Z. Pasternak, O. Freidenberg are revealed. Presented and characterized appeals (in the initial and middle positions), attributive and substantive lexemes, which are the most significant elements of the language when creating the image of the addressee. The attributive lexemes, deliberately selected by the author to create a certain communicative image, are revealed and described. They acquire different meanings depending on the lexical-semantic and grammatical environment and give the image of the addressee certain features inherent only in him. It is established that when creating an image of an addressee, the author actively uses abstract nouns. They are introduced into the text to characterize the positive traits of the recipient’s personality, reflect the author's vision and perception, and participate in the realization of such a method of influencing the addressee as praise.
Keywords: language tools; addressee’s image; epistolary text; B. Pasternak; E. Pasternak; M. Tsvetaeva; Z. Pasternak; O. Freidenberg; appeal; attributive lexemes; substantive lexemes